Kinematic factors determining differences in performance in the start phase of sprint swimming: Comparisons among Japanese and non-Japanese elite swimmers - Akashi, K.; Matsuda, Y. (Japan Journal of Physical Education, Health and Sport Sciences, 2022)
The purpose of this study was to clarify the kinematic factors determining differences in performance in the start phase of sprint swimming (from the start signal to the first 15 m). For this purpose, we compared the start phases of 19 male and 18 female elite swimmers showing high performance over short-distance events in Japan. The results showed that, for both men and women, the time from 5 m to 15 m had a greater effect on the 15 m time than the time from the start signal to 5 m. In other words, swimming velocity during the underwater kick and stroke transition was found to be important. In addition, the average horizontal velocity at 4 m - 5 m was related to the 15 m time for both men and women, but the horizontal take-off velocity was related to the 15 m time only for men. On the other hand, the horizontal take-off velocity of Japanese swimmers tended to be lower than that of foreign swimmers documented in previous studies. These results suggest that the factors requiring improvement in the starting phase differ according to gender and competition level.